2021
DOI: 10.1007/s00531-020-01971-0
|View full text |Cite
|
Sign up to set email alerts
|

Petrographic and geochemical characterization of the Middle‒Upper Jurassic Fe–Mn crusts and mineralizations from Monte Inici (north-western Sicily): genetic implications

Abstract: Fe–Mn concretions and mineralizations, associated with condensed horizons and hardground, are significant archives in ancient carbonate rocks. Their petro-chemical study allows an assessment of the palaeoenvironmental context in which they were formed also connected to their biotic or abiotic origin. At the western side of the Monte Inici (Fornazzo section, north-western Sicily) a well exposed outcrop of condensed pelagic limestones (Rosso Ammonitico facies: Middle‒Upper Jurassic) is well-known and thoroughly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 118 publications
0
6
0
Order By: Relevance
“…This finding is relevant in various environments. For instance, siderophores have been implicated in the formation of Fe–Mn nodules in sediments in marine environments. Furthermore, although Mn abundance is an order of magnitude lower than Fe abundance in soil, the impacts of Mn chemistry in soil biogeochemical cycles can be similar or greater than that of Fe. Our data suggest that siderophore-mediated redistribution of Mn can shift the surrounding redox environment toward more oxidizing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is relevant in various environments. For instance, siderophores have been implicated in the formation of Fe–Mn nodules in sediments in marine environments. Furthermore, although Mn abundance is an order of magnitude lower than Fe abundance in soil, the impacts of Mn chemistry in soil biogeochemical cycles can be similar or greater than that of Fe. Our data suggest that siderophore-mediated redistribution of Mn can shift the surrounding redox environment toward more oxidizing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the Noonday Formation has been interpreted as a marine carbonate platform with submarine canyons and dissecting the platform edge (Creveling et al, 2016), but that interpretation is not supported by petrographic, geochemical, granulometric, and crystallographic observations of the previous paragraphs. Carbonate shrubs in the Noonday Formation have been attributed to encrusting and interstitial marine microbial films (Fraiser & Corsetti, 2003), but careful examination of these features presented in the following paragraphs reveals much greater size and complexity than known in microbial films (Guido et al, 2016;Heim et al, 2017;Scopelliti & Russo, 2021). Neither field, petrographic, geochemical, nor fossil evidence support interpretation of the Noonday Formation as marine.…”
Section: Ravinement Surfacesmentioning
confidence: 99%
“…Noonday Formation tubestones have been compared with stromatolites, acknowledging that they differ fundamentally as concave-up laminae (Corsetti & Grotzinger, 2005). The various fractally branching structures of the Noonday Formation have also been compared with "marine carbonate shrubs", such as Frutexites (Fraiser & Corsetti, 2003), but have a more complex structure of internally Genuine Frutexites has the appearance of pyrolusite dendrites of fractally arranged small crystals, induced by activity of unicellular iron-manganese oxidizing bacteria (Guido et al, 2016;Heim et al, 2017;Scopelliti & Russo, 2021), but opaque grains are rare in the Noonday Formation. Ganarake lacks the histology of fossil calcareous algae, the box-like cells of rhodophytes, the verticillate structure of dasyclads, and the loose fountaining structure of chlorophytes (Wray, 1977;Flügel, 1977).…”
Section: Systematic Paleontologymentioning
confidence: 99%
“…Granite was widely distributed in the PRD, leading to quaternary soil with loose accumulation [23]. Previous studies have shown that limestone and sand shale are Mn-rich parent rocks [37,38]. The specific humid climate conditions present in the PRD accelerate the weathering process of parent rocks, and thus HMs are easily released from this natural source.…”
Section: Source Apportionment By Pca-mlr Modelmentioning
confidence: 99%